Penetapan Kadar Surfaktan Anionik pada Deterjen Cuci Cair Secara Metode Titrimetri - Wibisono, Ika Candrika (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2018)
Washing liquid detergent is a one type clothes are cleaning needed by the community, good by the household, industry, hospitality, restaurant and others. One type of component in liquid washing detergent is a anionic surfactant. Based on SNI 06-4075-1996 concerning Liquid Wash Detergents, the minimum quality requirement for anionic surfactants levels is 15% - 35%. Analysis the surfactant anionic levels of this experiment take method titrimetry. Principal on method titrimetry speficially, anionics surfactants with text example hydrolyzed with sulfuric acid form cationic and anionic mixture. Anionics surfactants derived from results reaction between the ethanol and sulfuric acid which sulfuric ethanol. Titration with sulfuric acids until the color solution change from pink to bluish gray. Anionic surfactants levels the which obtained from each example of A-D in a row is a 17,43%, 7,64%; 8,89%; 8,64%. Anionics Surfactants that is a satisfy the meminimum quality requirement, namely 15%-35%.